Colletotrichum leaf spot disease in Naravelia zeylanica and its distribution in Bhadra Wildlife Sanctuary, India - and M.B. SHIVANNA*, K.G. SOMASHEKHARA ACHAR (Indian Phytopathology, 2013)
Naravelia zeylanica is a medicinally important climber growing extensively in the natural habitat of Bhadra Wildlife Sanctuary (BWLS) in Karnataka. A study was taken up to determine fungal diseases caused in the species, and the diseased incidence and severity due to pathogen in all forest regions of the sanctuary althrough the seasons. The plant is infected considerably by Colletotrichum dematium throughout the year in 11 out of 12 state forest regions of BWLS. The identity of organism was confirmed and pathogenicity was determined. Results of the field study indicated that the disease incidence and severity due to C. dematium ranged from 3.3 to100% and 1.7 to 51.7%, respectively, in the study area for the entire study period. The spatial distribution of leaf spot disease in N. zeylanica was determined by the binary form of Taylor’s power law. The analysis indicated that the disease is distributed heterogeneously (p<0.001) in eight forest regions and homogeneously (p<0.001) in two state forest regions of the sanctuary. The alkaloid content in foliages decreased upon infection, while the flavonoid, phenol and steroid contents increased upon infection.